Development Of Enterprise Human System Modelling Framework In Support Of Cellular Manufacturing Lean Operation - Abdullah, Rohana; Hashim, Hanizam; Abd Rahman, Md Nizam; Salleh, Mohd Rizal (Penerbit Universiti, UTeM, 2018)
Static or enterprise model stems from the need to understand the potential effect of certain parameters on the system performance. This paper describes the development of the human system framework focusing on the aspects of human attributes and human dynamics in the effort to achieve a leaner operation in the cellular manufacturing operation. The aim of this study is to propose a model to improve the accuracy in modelling human workload and competency based on the theoretical frameworks. Existing frameworks and models were reviewed and two models (M2M mathematical model and CIMOSA) were identified as the theoretical framework for this study. A new human system framework was designed with the improvement on the operator competency accuracy using Maynard Operational Sequence Technique. The new framework was also primarily designed to suit the cellular manufacturing environment through the inclusion of the equipment competency. As a result, company’s management is expected to be better informed on operator utilisation, man-machine configuration and operator non-value added activities.